Health Literacy and Recall of Postoperative Instructions in Patients Undergoing the Lapidus Procedure. Issue 3 (23rd September 2020) - Garfinkel, Jonathan H.; Hummel, Amelia; Day, Jonathan; Roney, Andrew; Jones, Mackenzie; Rosenbaum, Andrew; Ellis, Scott J.
Background: Active participation in patients' own care is essential for success after Lapidus procedure. Poor health literacy, comprehension, and retention of patient instructions may be correlated with patient participation. Currently, there is no objective measure of how well patients internalize and retain instructions before and after a Lapidus procedure. We performed this study to assess how much of the information given to patients preoperatively was able to be recalled at the first postoperative visit. Methods: All patients between ages 18 and 88 years undergoing a Lapidus procedure for hallux valgus by the senior author between June 2016 and July 2018 were considered eligible for inclusion. Patients were excluded if they had a history of previous bunion surgery or if the procedure was part of a flatfoot reconstruction. Patients were given written and verbal instructions at the preoperative visit. Demographic and comprehension surveys were administered at their first visit approximately 2 weeks postoperatively. A total of 50 patients, of which 42 (84%) were female and 43 (86%) had a bachelor's degree or higher, were enrolled. Results: Mean overall score on the comprehension survey was 6.2/8 (±1.2), mean procedure subscore was 1.8/3 (±0.64), and mean postoperative protocol subscore was 4.4/5 (±0.8). The most frequently missed question asked patients to identify the joint fused in the procedure. Conclusion: Although comprehension and retention of instructions given preoperatively was quite high in our well-educated cohort, our findings highlight the importance of delivering clear instructions preoperatively and reinforcing these instructions often. Level of Evidence: Level II, prospective cohort study.